(untitled) (Journal of Pharma Insights and Research, 2025)
The proliferation of falsified and substandard medicines within global pharmaceutical supply chains presents a formidable threat to public health, directly exacerbating the crisis of antimicrobial resistance (AMR). The complicated and often opaque nature of these supply networks creates vulnerabilities that are exploited for the infiltration of fraudulent products. Falsified antimicrobials, which frequently contain sub-therapeutic concentrations of active pharmaceutical ingredients or incorrect components, fail to eliminate targeted pathogens. This inadequate treatment exerts selective pressure on microbial populations, fostering the survival and propagation of drug-resistant strains. Consequently, the efficacy of legitimate antimicrobial therapies is undermined, leading to prolonged illnesses, increased mortality, and escalating healthcare costs. Addressing this convergence of threats requires a multi-pronged strategy. Modern technologies such as blockchain, artificial intelligence (AI), and the Internet of Things (IoT) offer robust mechanisms for enhancing traceability, transparency, and authentication from manufacturer to patient. However, the successful implementation of these technologies is contingent upon surmounting significant financial, infrastructural, and regulatory hurdles, particularly in low- and middle-income countries (LMICs) where the burden is greatest. Strengthening international regulatory harmonization, bolstering national enforcement capacities, and fostering public-private partnerships are imperative. A collaborated global effort is essential to secure the integrity of the pharmaceutical supply chain, thereby preserving the utility of critical antimicrobial medicines and safeguarding global health security against the silent pandemic of AMR